Activation of respiratory Complex I from Escherichia coli studied by fluorescent probes. Issue 1 (January 2017) - Belevich, Nikolai; Belevich, Galina; Chen, Zhiyong; Sinha, Subhash C.; Verkhovskaya, Marina
Abstract: Respiratory Complex I from E. coli may exist in two interconverting forms: resting (R) and active (A). The R/A transition of purified, solubilized Complex I occurring upon turnover was studied employing two different fluorescent probes, Annine 6+, and NDB-acetogenin. NADH-induced fluorescent changes of both dyes bound to solubilized Complex I from E. coli were characterized as a function of the protein:dye ratio, temperature, ubiquinone redox state and the enzyme activity. Analysis of this data combined with time-resolved optical measurements of Complex I activity and spectral changes indicated two ubiquinone-binding sites; a possibility of reduction of the tightly-bound quinone in the resting state and reduction of the loosely-bound quinone in the active state is discussed. The results also indicate that upon the activation Complex I undergoes conformational changes which can be mapped to the junction of the hydrophilic and membrane domains in the region of the assumed acetogenin-binding site.